Body mass index and risk of liver cirrhosis in middle aged UK women: prospective study. (11th March 2010) - Liu, Bette; Balkwill, Angela; Reeves, Gillian; Beral, Valerie; ,
Abstract : Objective To determine the relation between body mass index (BMI) and liver cirrhosis and the contribution that BMI and alcohol consumption make to the incidence of liver cirrhosis in middle aged women in the UK. Design Prospective cohort study (Million Women Study). Setting Women recruited from 1996 to 2001 in NHS breast screening centres and followed by record linkage to routinely collected information on hospital admissions and deaths. Participants 1 230 662 women (mean age 56 years at recruitment) followed for an average of 6.2 years. Main outcome measures Relative risk and absolute risk of first hospital admission with or death from liver cirrhosis adjusted for age, recruitment region, alcohol consumption, smoking, socioeconomic status, and physical activity. Results 1811 women had a first hospital admission with or died from liver cirrhosis during follow-up. Among women with a BMI of 22.5 or above, increasing BMI was associated with an increased incidence of liver cirrhosis: the adjusted relative risk of cirrhosis increased by 28% (relative risk 1.28, 95% confidence interval 1.19 to 1.38; P<0.001) for every 5 unit increase in BMI. Although the relative increase in the risk of liver cirrhosis per 5 unit increase in BMI did not differ significantly according to the amount of alcohol consumed, the absolute risk did. Among women who reported drinking less than 70 g alcohol per week, the absolute risk of liver cirrhosis per 1000 women over five years was 0.8 (0.7 to 0.9) for those with a BMI between 22.5 and 25 and 1.0 (0.9 to 1.2) for those with a BMI of 30 or more. Among women who reported drinking 150 g alcohol or more per week, the corresponding figures were 2.7 (2.1 to 3.4) and 5.0 (3.8 to 6.6). Conclusions Excess body weight increases the incidence of liver cirrhosis. In middle aged women in the UK, an estimated 17% of incident or fatal liver cirrhosis is attributable to excess body weight. This compares with an estimated 42% attributable to alcohol.